EDUKASI POLA HIDUP SEHAT DI MASA PANDEMI DI DESA SURABAYA TIMUR - Erikson Saing,; Mutia Mawardah, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
According to Ahmad D Marimba Education is a conscious guidance carried out by the education, both in physical and spiritual development to become better. So, this education can make things better. Based on observation data, in East Surabaya Village, the local population has no or lack of understanding of healthy lifestyles, especially in applying them in daily life. Based on interview data, it is true that residents in this village do not understand and have not implemented a healthy lifestyle properly starting from maintaining cleanliness and implementing health protocols. Because, if healthy lifestyle during this pandemic not implemented well, it can open up space for the spread of the covid-19 virus and lack of socialization related to healthy lifestyle in this village. According to Azhar Arsyad. Poster is a two-dimensional visual media that contains images and short written messages that aim to convey special things and able to influence people who see it. The activity which was held in East Surabaya Village was attended by 34 families. Result shows that the local community can understand what a Healthy Lifestyle is and how to apply it during the current pandemic.